Exploring Links Between Industrialization, Urbanization, and Chinese Inflammatory Bowel Disease - Cui, Guanglin; Liu, Hanzhe; Xu, Gang; Laugsand, Jann-Birger; Pang, Zhigang (Frontiers in Medicine, 2021)
Background: Evidence is emerging that the incidence of inflammatory bowel diseases (IBD) is dramatically increased in China, but with a geographic variation. Objectives: We performed a review to summarize the link of accelerated industrialization, urbanization to changing trends in the incidence of IBD over the last three decades. Methods: An electronic database search was performed in PubMed, Medline, EMBASE and Google Scholar (for English literature) and the China Science Periodical Database in Wanfang Data (for Chinese literature) from January 1990 to June 2020. Results: By systematically analyzing the changing trends of gross domestic product (GDP) or GDP per capita, population migration from rural areas to cities and increasing incidence of IBD in parallel in different Chinese regions, an association between accelerated industrialization and urbanization and rising rate of IBD was shown. In which, rates of IBD incidence were higher in provinces with a high value of GDP per capita than those provinces with a low value of GDP per capita. Analysis of available epidemiological data revealed that the incidence of IBD was rising in parallel with increasing trends of both gross products of industry and urban population in Yunnan Province in a 14-year interval. Further evidence suggested that industrialization- and urbanization-induced subsequent changes in environmental factors, e.g., Westernized dietary habits and obesity, and work-related stress, might contribute to the increased risk of IBD in China. In addition, the preliminary results showed that urbanization and Westernized dietary habits might induce significant changes in gut microbiota profile that are possibly to increase the risk for IBD in Chinese. Conclusions: Existing evidence to suggest that accelerated industrialization/urbanization is associated with the increasing incidence of IBD in China, which provides novel insights to study the possible mechanisms for the recent increasing incidence of IBD in newly industrialized and urbanized developing countries. In the future, the interaction between relevant environmental factors e.g., air/water pollution and IBD susceptibility genes in Chinese should be examined.